Distributed Movement Control for Building a Ring in Mobile Wireless Sensor Networks - Jian Chen; Jie Jia; Yingyou Wen; Dazhe Zhao (International Journal of Distributed Sensor Networks)
Many applications in wireless sensor networks require some sensors to form a ring or multiring-based shape in the target area, such as intrusion detection, border surveillance, routing overlay formation, and network full coverage. In this paper, we study the problem of sensor redistribution to build a ring-based shape for mobile sensor networks. We first give the theoretical analysis on what is optimal sensor movement with the given random deployment. Then, we propose a fully distributed movement control algorithm to achieve ring-based shape for mobile sensor networks. We formally prove that our algorithm can achieve a ring-based distribution within finite time. We also present the procedures of applying our algorithm to form multiring-based distribution. Finally, we present extensive simulations to verify that our approach outperforms other schemes in terms of both the moving distance and convergence time.